The physical and physiological demands of a singles tennis match for junior state-level players - Syahrul, R.M.; Asok, K.G.; Chen, C.K. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The intermittent nature of the game, court surface, equipment, tactical approach, duration of the match and environmental factors may affect the physical and physiological demands of playing tennis. Although previous studies have investigated the physical and physiological demands during singles tennis play at various levels, there is a very limited information on junior tennis players. Thus, the purpose of this study was to determine the physical and physiological demands during singles tennis play of junior players.. Methods Ten male state-level tennis players participated in this study and age, height, weight, VO2max and heart rate at anaerobic threshold (HRAT) of the players was collected. This study was conducted in 2 phases: laboratory test (Phase I), and simulated match (Phase II). In Phase I, subjects underwent an incremental treadmill exercise (Bruce Protocol) until volitional fatigue in order to determine their maximum oxygen consumption (VO2max), maximum heart rate (HRmax) and post exercise blood lactate concentration (LApost). Before the test began, subjects were equipped with a portable metabolic measurement and heart rate monitor. Whole blood samples were obtained from the fingertip before (LApre) and after (LApost) the exercise. In Phase II, all subjects played a simulated singles match against an opponent of similar standard based on singles rankings within the local state tennis competition. The match duration was set for 60 minutes by using the `best of three sets` match format. Heart rate responses were recorded throughout the match, whereas whole blood samples were collected before and after the match. All matches were recorded using digital video camera for further match analysis such as the number of forehand and backhand strokes, average duration and number of rallies, and the work-rest pauses ratio during the simulated match. Results Fractional utilisation of VO during the simulated match play was found to be 69.3 + 9.8%. Due to the intermittent nature of the game and the work-rest ratio of 1 : 2.2, the post-match blood lactate was found to be 3.21 + 0.2 mmol·L ¹, reflecting an aerobic dominance of the game. In addition, the mean match heart rate (154.3 + 15.4 beats·min ¹) was lower than the mean HRAT, signifying a lower blood lactate level less than 4.0 mmol·L ¹ in a tennis match. During the longest rally, the mean heart rate of the players was 174.9 + 3.1 beats·min ¹, which corresponded to 84.5 + 2.2% of VO2m a x . On the other hand, rallies per game, mean rally duration and strokes per rally were found to be 5.7 + 2.4, 4.5 + 1.5 seconds and 2.8 + 0.8 shots respectively. Discussion / Conclusions This study concluded that state-level tennis players possessed a moderately good aerobic capacity. This can be improved to the international standard through endurance and intermittent types of training. Improvement in VO 2max may increase the playing intensity of the match, as well as a better recovery in the rest pauses and also delay the onset of fatigue during tennis play.